The volumetric fraction of inorganic particles and the flexural strength of composites for posterior teeth - Adabo, Gelson Luis [UNESP]; Cruz, CAD; Fonseca, Renata Garcia [UNESP]; Vaz, Luis Geraldo [UNESP] (Elsevier B.V., 2003)
Objective. To evaluate the content of inorganic particles and the flexural strength of new condensable composites for posterior teeth in comparison to hybrid conventional composites.Method. The determination of the content of inorganic particles was performed by mass weighing of a polymerized composite before and after the elimination of the organic phase. The volumetric particle content was determined by a practical method based on Archimedes' principle, which calculates the volume of the composite and their particles by differential mass measured in the air and in water. The flexural. strength of three points was evaluated according to the norm ISO 4049:1988.Results. The results showed the following filter content: Alert, 67.26%; Z-100, 65.27%; Filtek P 60, 62.34%; Ariston pHc, 64.07%; Tetric Ceram, 57.22%; Definite, 54.42%; Solitaire, 47.76%. In the flexural strength test, the materials presented the following decreasing order of resistance: Filtek P 60 (170.02 MPa) > Z-100 (151.34 MPa) > Tetric Ceram (126.14 MPa) = Alert (124.89 MPa) > Ariston pHc (102.00 MPa) = Definite (93.63 MPa) > Solitaire (56.71 MPa).Conclusion. New condensable composites for posterior teeth present a concentration of inorganic particles similar to those of hybrid composites but do not necessarily present higher flexural strength. (C) 2003 Elsevier B.V. Ltd. Alt rights reserved.
Keywords: composite resins; physical characteristics; dental esthetics